Peningkatan Kemampuan Berpikir Kreatif Siswa melalui Model Pembelajaran Inkuiri Terbimbing pada Siswa Kelas XI MIA 1 SMA Negeri Colomadu Karanganyar Tahun Pelajaran 2015/2016 - Redza Dwi Putra; Yudi Rinanto; Sri Dwiastuti; Irwan Irfa’i (Universitas Sebelas Maret, 2016)
The aim of the research to increase creative thinking ability of students by applying guided inquiry learning at studentsgrade XI MIA 1 SMA Negeri Colomadu Karanganyar in the academic year 2015/2016. The research was classroom action research which held on 2 cycles with on research target achievement is an increase as big as 30% from baseline on the students creative thingking ability. Each cycle consisted of 4 base steps: Planning, Action, Observation, and Reflection. Subject of the research was 34 students of Grade X MIA 1 SMA Negeri Colomadu Karanganyar consisting of 12 boys and 22 girls. Data collecting technique of the research was done essay test to measured students creative thinking ability, creative atittude observation sheet to measured students creative attitude, interviewto evaluate the response of students and teachers to the learning activities, and photo documentation and video as authentic evidence of the learning process. Validation data technique used triangulationtechnique. Analysis data technique used descriptive analysis technique. The results of research showed an increase in each of these aspects of creative thinking ability of students is calculated from the Pre-Cycle, Cycle I, until the Cycle II with details: Fluency aspect (29.4%, 48.2%, and 68.8% ) with an increase as big as 39.4%; Flexibility aspect (28.5%, 48.5% and 69.4%) with an increase as big as 40.9%; Originality aspect (27.1%, 45.3% and 65.3%) with an increase as big as 38.2%; Elaboration aspect (25.3%, 47.6% and 67.9%) with an increase as big as 42.6%.Based on the results was obtained, it can be concluded that guided inquiry learning is able to increase the students creative thingking ability at XI MIA 1 SMA Negeri Colomadu Karanganyar in Academic Year 2015/2016 with an increase as big as 40,3% (19,8% increase from Pre-Cycle until the first cycle, and 20,5% increase from the Cycle I to the Cycle II).Keywords: creative thinking ability, guided inquiryPeningkatan Kemampuan Berpikir Kreatif Siswa melalui Model Pembelajaran Inkuiri Terbimbing pada Siswa Kelas XI MIA 1 SMA Negeri Colomadu Karanganyar Tahun Pelajaran 2015/2016